COMBINING ABILITY AND HETEROSIS IN QUALITY PROTEIN MAIZE - P. K. SINGH,; A. K. SINGH,; J. P. SHAHI,; R. RANJAN, (The Bioscan, 2012)
A half diallel set of eight newly developed white kernel colour quality protein maize inbred lines were utilized to evaluate combining ability and heterosis for yield and its components characters. Analysis of variance revealed significant differences among the parents and experimental hybrids for all the characters except ear diameter. Combining ability analysis revealed that estimate of specific combining ability (SCA) variances were higher than general combining ability (GCA) variances for all the traits under study, indicating predominance of non-additive gene action of these traits. The parents HUZQPM 3-2, HUZQPM 6-2 and HUZQPM 5 were identified as good combiners for yield and its related traits. The best experimental hybrids, on the basis of per se performance, SCA effect and standard heterosis for grain yield per plant and two to five of its component was HUZQPM 1-1 X HUZQPM 3-2 followed by HUZQPM 1-1 X HUZQPM 5 that yielded 51.28 and 33.16 per cent more grain yield, respectively over best commercial check hybrid HQPM 1. Result suggested that these crosses may be exploited for commercial cultivation in North East Plane Zone (NEPZ) of maize growing areas after testing over the location.